PENGARUH PERSEPSI SISWA TENTANG PROFESI GURU DAN LINGKUNGAN KELUARGA TERHADAP MINAT SISWA MENJADI GURU - Sintha Widyaningrum; Ignatius Bondan Suratno (Jurnal Pendidikan Ekonomi dan Akuntansi, 2022)
This research aimed to determine whether there was a positive influence of students’ perceptions on teaching profession and family environment toward students’ interest in becoming teachers in class X and XI Natural Science Mathematics and Social Studies majors at SMA Negeri 1 Depok Yogyakarta in 2022.This type of research was descriptive research using quantitative methods. The population in this study was all students of class X and XI majoring in Natural Science Mathematics and Social Studies at SMA Negeri 1 Depok Yogyakarta, totaling 431 students. The sample of this research was 203 students taken using proportional stratified random sampling. The data collection in this research used a questionnaire. The data were analyzed using multiple linear regression analysis.The result of the research showed that students’ perceptions on teaching profession and family environment together had a positive influence on students’ interest in becoming teachers. The result of this research was evidenced by the calculated F value of 8.992 and the significance value of 0.000.Keywords: students’ perceptions on teaching profession, family environment and students’ interest in becoming teachers.